2010
DOI: 10.3171/2010.8.peds103
|View full text |Cite|
|
Sign up to set email alerts
|

Predicting who will benefit from endoscopic third ventriculostomy compared with shunt insertion in childhood hydrocephalus using the ETV Success Score

Abstract: Object The authors recently developed and internally validated the ETV Success Score (ETVSS)—a simplified means of predicting the 6-month success rate of endoscopic third ventriculostomy (ETV) for a child with hydrocephalus, based on age, etiology of hydrocephalus, and presence of a previous shunt. A high ETVSS predicts a high chance of early ETV success. In this paper, they assess the clinical utility of the ETVSS by determining whether long-term survival outcomes f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
159
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 226 publications
(170 citation statements)
references
References 20 publications
8
159
1
2
Order By: Relevance
“…Various classification systems are emerging not only to help predict outcome after endoscopic procedures for hydrocephalus, but also to aid in the selection of appropriate patients to maximize positive outcomes. 25,[42][43][44][45] The most common indication for ETV is aqueductal stenosis, either from congenital narrowing of the aqueduct or obstructive tumors such as tectal gliomas 46 and obstructive cysts. 47,48 Other indications include the fenestration of loculated compartments, 49,50 ventriculoperitoneal shunt malfunction, 26,27 and preresectional ETV for posterior fossa tumors.…”
Section: Hydrocephalusmentioning
confidence: 99%
“…Various classification systems are emerging not only to help predict outcome after endoscopic procedures for hydrocephalus, but also to aid in the selection of appropriate patients to maximize positive outcomes. 25,[42][43][44][45] The most common indication for ETV is aqueductal stenosis, either from congenital narrowing of the aqueduct or obstructive tumors such as tectal gliomas 46 and obstructive cysts. 47,48 Other indications include the fenestration of loculated compartments, 49,50 ventriculoperitoneal shunt malfunction, 26,27 and preresectional ETV for posterior fossa tumors.…”
Section: Hydrocephalusmentioning
confidence: 99%
“…They concluded that a high ETV success score correlated with a greater reliability of ETV compared to CSF shunts immediately after surgery, whereas this benefit was not attained among lower ETV success scorers until 3 to 6 months after surgery [30]. In determining the ETV success score, patient age was implicated as the strongest predictor of success; older children (>6 months) typically experienced superior outcomes versus their younger counterparts [31].…”
Section: Success Rates and Determinants Of Successmentioning
confidence: 99%
“…A shunt cohort contained patients collected from 2 separate groups, The Shunt Design Trial (recruited 1993-1995) and the Endoscopic Shunt Insertion Trial (recruited 1996-1999). 14 Kulkarni and colleagues found that for patients with a high ETVSS, ETV had a lower risk of failure than CSF shunting beginning immediately after surgery and that it remained durable over time. For patients with a moderate ETVSS, ETV had a higher initial failure rate that became more favorable with time.…”
mentioning
confidence: 99%
“…In the accompanying thoughtful article, 14 Kulkarni and colleagues have attempted to shed some light on this problem, using a quantitative scale they developed, the ETV Success Score (ETVSS), to evaluate the outcome of ETV compared to CSF shunt placement. The ETVSS was initially created to predict the effectiveness of ETV using only 3 parameters: age of the patient, etiology of the hydrocephalus, and the presence of a previous shunt, with a high score predictive of a good outcome.…”
mentioning
confidence: 99%